SOME TOPICAL ISSUES IN THE PROCESS OF TRANSLATION OF TEXTS IN THE FIELD OF MECHANICAL ENGINEERING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyses some of the problems in the translation of texts in the field of Mechanical Engineering. Such problems arise due to the fact that the technical vocabaly differs from the terms in colloquial and literary texts. But grammatical norms remain in place. Engineers in Mechanical Engineering are required to learn and keep in mind many of the terms related to the field.